2018
DOI: 10.1159/000495900
|View full text |Cite
|
Sign up to set email alerts
|

PGK1 is a Potential Survival Biomarker and Invasion Promoter by Regulating the HIF-1α–Mediated Epithelial-Mesenchymal Transition Process in Breast Cancer

Abstract: Background/Aims: Glycolysis, a multi-step enzymatic reaction, is considered to be the root of cancer development and progression. The aim of this study is to figure out which glycolysis enzyme participates in the progression of breast cancer and its possible mechanisms. Materials: We firstly screened out PGK1 by performing an RT-PCR array of glycolysis-related genes in three paired breast cancer samples, and further investigated PGK1 using TCGA and our own database. The effect and mechanism of PGK1 on cell inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 29 publications
2
49
0
Order By: Relevance
“…The results indicated that HIF‐2α co–immunoprecipitated with proteins, including PGK1 (Appendix ), ALDOC, and ENO2, etc. Evidence suggested that PGK1, which was considered as a vital kinase in cellular activity and a target gene of HIF‐1α, could form a positive feed‐forward loop with HIF‐1α and, thus, stimulated breast cancer progression and metastases . However, we discovered that PGK1 could form a complex with HIF‐2α using silver staining and mass spectrometry, which seemed interesting.…”
Section: Resultsmentioning
confidence: 89%
“…The results indicated that HIF‐2α co–immunoprecipitated with proteins, including PGK1 (Appendix ), ALDOC, and ENO2, etc. Evidence suggested that PGK1, which was considered as a vital kinase in cellular activity and a target gene of HIF‐1α, could form a positive feed‐forward loop with HIF‐1α and, thus, stimulated breast cancer progression and metastases . However, we discovered that PGK1 could form a complex with HIF‐2α using silver staining and mass spectrometry, which seemed interesting.…”
Section: Resultsmentioning
confidence: 89%
“…To measure the performance and determine the reliability of OSbrca, we have collected previously published prognostic biomarkers of breast cancer (Table S1) and tested their prognostic potency in OSbrca. Fu et al have demonstrated that PGK1 was overexpressed in tumor tissue and was an indication of worse survival biomarker in breast cancer (13). Using OSbrca, we showed that PGK1 gene was indeed a poor survival biomarker in breast cancer cohorts (Figure 1).…”
Section: Evaluation Of the Previously Reported Prognostic Biomarkers mentioning
confidence: 68%
“…This signature includes 44 metabolic genes that are essential for EMT but not cell proliferation, involving metabolism regulation of glucose, lipid, and nucleotide [48]. Noticeably, functional studies demonstrated that knockdown of PGK1 could reverse the EMT process to inhibit invasion of BC cells [21]. An investigation on hepatocellular carcinoma indicated that G6PD could activate the STAT3 pathway to promote EMT and further favor cancer metastasis [49].…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that up-regulated PGK1 and G6PD in BC tissues is associated with a high risk of recurrent metastasis and poor survival of patients. The mechanisms include the enhancement of energy supply and activation of the HIF-1α pathway in cell migration and invasion [21,22]. Therefore, PGK1 and G6PD are potential markers to profile the metabolic activity of CTCs and further indicate the functional CTCs subtypes for BC patients.…”
mentioning
confidence: 99%